2015
DOI: 10.1002/joc.4255
|View full text |Cite
|
Sign up to set email alerts
|

On the controlling factors for the variability of carbon dioxide flux in a heterogeneous urban environment

Abstract: Local heterogeneity of CO 2 sources and sinks is a key factor for the variability of carbon dioxide flux (F C ) in urban areas. Information on the urban structure around a site, especially the related emission characteristics, is thus of great importance to the understanding of observed F C . Strong spatially confined sources like major roads inhibit a direct correlation of F C to area-averaged features of the urban structure and may lead to a heavily biased signal.Four years of F C measured at Basel Aeschenpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…Recently, many studies focused on approaches toward a better understanding of the linkage between carbon dioxide (CO 2 ) emissions in urban environments and their controlling factors [ Christen et al , ; Contini et al , ; Lietzke et al , ; Velasco et al , ]. Modeling approaches are an important step forward to transform information from point measurement to larger spatial (e.g., city) scales, which is essential to achieve a comprehensive picture of the entire urban metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, many studies focused on approaches toward a better understanding of the linkage between carbon dioxide (CO 2 ) emissions in urban environments and their controlling factors [ Christen et al , ; Contini et al , ; Lietzke et al , ; Velasco et al , ]. Modeling approaches are an important step forward to transform information from point measurement to larger spatial (e.g., city) scales, which is essential to achieve a comprehensive picture of the entire urban metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…As the eddy covariance (EC) method for the determination of turbulent fluxes of mass and energy only became a widely applicable method in urban areas since the late nineties, multiyear studies able to catch long‐term trends and interannual variabilities are still rare. A comprehensive overview of recent studies on urban CO 2 fluxes ( F C ) is given in Lietzke et al [], whereas the longest time series reported in literature cover at most 5–6 years [ Crawford et al , , Gioli et al , ]. In contrast, there are numerous long‐term data sets of CO 2 mole fraction ( ρ C ) and F C from natural terrestrial ecosystems (e.g., FLUXNET, http://www.fluxdata.org) or remote background concentration measurements (e.g., Carbon Dioxide Information Analysis Center, http://cdiac.ornl.gov/) and a variety of corresponding studies [ Hofmann et al , ; Liu et al , ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies, however, focused on seasonal variations, not diurnal-scale variations. Revealing the controlling factors of diurnal scale variations is still limited (Velasco et al 2009;Ward et al 2013;Ward et al 2015;Lietzke et al 2015).…”
Section: Introductionmentioning
confidence: 99%